1980
DOI: 10.1111/j.1348-0421.1980.tb02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Nontoxigenic Variants Associated with Enhanced Sporulation and Alteration in the Cell Wall from Clostridium botulinum Type A 190L by Treatment with Detergents

Abstract: Nontoxigenic variants were isolated from Clostridium botulinum type A strain 190L after treatment with detergents such as deoxycholate, sodium dodecyl sulfate, Tween 80 and Brij-58. Deoxycholate was most effective for obtaining the variants. The variants exhibited a markedly increased frequency of sporulation compared with the oligosporogenic parent strain. The cell wall of the parent strain was composed of an outer layer and an inner layer, whereas that of the variants lost the outer layer. After treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…We reported the isolation of nontoxigenic variants associated with loss of lysogeny, enhanced sporulation and deficiency of the outer wall layer in the presence of detergents, and we suggested that the genes concerned with these phenotypes would be integrated either into the prophage genome or into the neighboring chromosomal genome linked with the prophage genome (30). We have found here that there is no direct relationship between lysogeny and toxigenicity in type A strain 190L, though possible involvement of noninducible defective prophage in toxin production has not been excluded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reported the isolation of nontoxigenic variants associated with loss of lysogeny, enhanced sporulation and deficiency of the outer wall layer in the presence of detergents, and we suggested that the genes concerned with these phenotypes would be integrated either into the prophage genome or into the neighboring chromosomal genome linked with the prophage genome (30). We have found here that there is no direct relationship between lysogeny and toxigenicity in type A strain 190L, though possible involvement of noninducible defective prophage in toxin production has not been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for induction with MC was essentially identical to that reported earlier (30). MC (Kyowa Hakko Kogyo Co., Ltd., Tokyo) was added to early log-phase cultures of strain 190L in GYPT medium to give final concentrations of 0.1 to 10 p,gjml and further incubated at 37 C for 6 hr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurotoxin formation in C. botulinum has been reported to be unstable (Gunnison and Meyer 1929b;Lewis and Hill 1947;Schantz and Johnson 1992;Takumi et al 1980;Townsend 1929), and the genes of the neurotoxin gene complex can be associated with mobile elements in certain serotypes (Eklund et al , 1989Hauser et al 1992Hauser et al , 1995Quinn and Minton 2001;Zhou et al 1993 (Table 1). resembling Clostridium baratii, and Clostridium butyricum producing botulinum-like neurotoxins have been isolated from infants with botulism (Aureli et al 1986;Hall et al 1985;Hatheway 1995;McCroskey et al 1986McCroskey et al , 1991Suen et al 1988b).…”
Section: Milestones In the Understanding Of Botulism And Tetanus Botumentioning
confidence: 99%